CSI Transactions on ICT - Raghavan, S.V.; SpringerLink (Online service) (New Delhi : Springer India : Imprint: Springer.)
The focus of CSI Transactions on ICT is on the practical implications of advances in information and communication technology and associated management issues. It is intended for all kind of professionals be it researchers, academicians, industry, government and policy makers. The journal will also serve domain experts in education, healthcare, management and agriculture who are making an attempt to utilize the vast potential of ICT in their respective fields and thereby bridge the digital divide. CSI Transactions will initially provide coverage on the following areas: Systems and Architecture Software Design and Performance Cyber and Information Security Education, Health and Agriculture Economics, Practice and Management Computing and Computational Science.
Keywords: Computer science; Input-output equipment (Computers).; Computer communication systems; Software engineering; Software Engineering/Programming and Operating Systems; Systems and Data Security; Computer Communication Networks; Input/Output and Data Communications; Computer Science, general